2015
DOI: 10.1016/j.antiviral.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leflunomide, Cidofovir and Ciprofloxacin on replication of BKPyV in a salivary gland in vitro culture system

Abstract: BK polyomavirus (BKPyV) is a known kidney tropic virus that has been detected at high levels in HIV-associated salivary gland disease (HIV-SGD), one of the most important AIDS associated oral lesions. BKPyV has been detected in HIV-SGD patient saliva and replicates in salivary gland cells in vitro. BKPyV antivirals are currently in wide use to guard against BKPyV mediated organ rejection in kidney transplant recipients. The goal of this study was to investigate the inhibitory effects of three such antiviral ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 49 publications
(95 reference statements)
2
25
1
Order By: Relevance
“…To-date, it has been shown that antiviral activity against BKV is displayed by cidofovir CMY001, leflunomide, lactoferrin and ciprofloxacin. The results confirm that the latter of the aforementioned drugs has the best effect, both in vivo and in vitro [3,[10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…To-date, it has been shown that antiviral activity against BKV is displayed by cidofovir CMY001, leflunomide, lactoferrin and ciprofloxacin. The results confirm that the latter of the aforementioned drugs has the best effect, both in vivo and in vitro [3,[10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 75%
“…The necessity to look for medicines against BKV was also noted by Jeffers-Francis et al [3]. In their research, they proved that in AIDS cases BK virus may be translocated to the salivary glands where it may cause HIV-associated salivary gland disease (HIV-SGD).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations